Water-smart farming: review of strategies, technologies, and practices for sustainable agricultural water management in a changing climate in West Africa - Frimpong, Felix; Asante, Maxwell Darko; Peprah, Clement Oppong; Amankwaa-Yeboah, Patricia; Danquah, Eric Owusu; Ribeiro, Priscilla Francisco; Aidoo, Atta Kwesi; Agyeman, Kennedy; Asante, Mary Otiwaa Osei; Keteku, Agbesi; Botey, Hillary Mireku (Frontiers in Sustainable Food Systems, 2023)
The global temperature increase of 1.1˚C over the past decade and human population growth are already escalating competition for water in locations where water is scarce, adversely affecting agriculture. Water-smart farming was developed to address challenges associated with the availability, access and use of agricultural water. It complements practices and goals related to agricultural water in climate-smart agriculture. It encompasses several climate-responsive food cropping systems, watersaving methods, tools, and technologies to grow food sustainably. Effective implementation of watersmart farming can ameliorate the pressing burden of agricultural water competition. Therefore, the conceptual framework of water-smart farming and its principal elements or ideology are introduced in this review. The major pillars of water-smart cropping, which include conditioning and improving the soil's capacity to capture and hold moisture, basic infrastructure for water harvesting, storage and use as nature-based cropping solutions were elaborated. Further examples of technologies and best practices in water-smart crop farming, such as breeding for drought-tolerant crop varieties, promoting dryland cropping systems, alternate wetting and drying technology, water drainage and control structures, rainwater harvesting, utilization of irrigation reservoirs, cover cropping and intercropping for enhancing soil moisture conservation were presented. The review also briefly shows the contribution of some of these best practices and adaptive technologies of water-smart cropping towards promoting water-saving methods used for growing rice, maize, legumes, cassava and peri-urban vegetables.